Aspectos ecológicos e fitossociológicos no entorno de nascentes em formações florestais do oeste de Santa Catarina - Floss, Paulo Alfonso (2011)
The present work was accomplished in the vicinity of water springs located in remaining portions of phytogeographical formations of the Western part of the Santa Catarina State in Brazil. Its main objective is to study the similarity between the formations and evaluate the relationship between the abundance of species and environmental variables. The database for this study was nine water springs, three from each phytogeographical formation. The sampling was done along two intercepting transects, with 26 plots of 10m x 20m (200m²) per spring. Every arboreal-arbustive species with a diameter at breast height greater than 5.0 cm was analyzed for this study. The environmental (edaphic) variables were obtained from samples of soil collected on each plot. Furthermore, the slope of the soil, sunlight exposure, geographical coordinates and altitude were measured and taken into account. The thesis is divided into five chapters: the first one has as its objective to determine, by means of grouping analysis, the similarity between forest formations of the area of study, indicating that the three formations are floristically different, which brings up the need of separate analysis of each forest formation given the vulnerability of the environments. In the second, third and fourth chapters the abundance of species was linked to the environmental variables (edaphic and topographic) present in each phytogeographical formation. The results unveiled a great variation of the vegetation amongst the springs, presenting particular indicator species for each one. Furthermore, the results made possible to determine the most flexible species, known as generalists, which are capable of developing in different environments. The fifth chapter has as its objective to recognize the functional ecological patterns of the arborescent community of portions of land in the vicinity of water springs of the phytogeographical formations of the Western part of the Santa Catarina State in Brazil.